Influence of HER2 expression on prognosis in metastatic triple-negative breast cancer—results from an international, multicenter analysis coordinated by the AGMT Study Group - Gampenrieder, S. P. (2023)
Funding Information: This project was initiated at the Endeavour Breast Project coordinated by Daiichi Sankyo (special thanks to Christian Opitz and Britta Mazur from Daiichi Sankyo). We thank all participants and the steering committee members of the Endeavour Breast Meeting who are not listed as co-authors ( Supplementary Table S4 , available at https://doi.org/10.1016/j.esmoop.2022.100747 ). The authors gratefully acknowledge the support from the AGMT office (particularly Mag. Katrin Dorfinger, Mag. Alexandra Keuschnig, Sebastian Schütz, and Dr. Daniela Wolkersdorfer) and all trial coordinators at the contributing centers. Publisher Copyright: © 2022 The Authors